Performance enhancement of turbocharger centrifugal compressor - Gunees, Mesut (My University, 2021)
In this thesis, the compressor part of a turbocharger system is examined. In the turbocharger compressor performance map provided by the supplier, the efficiencies are not at the desired levels. For this reason, it has been tried to increase the efficiency of the operating points selected on the compressor map under the same conditions. The first step of the study is to analyze the compressor side geometries (compressor wheel, diffuser and volute). In order to perform the analysis, three different operating points (OP1-OP2-OP3) are selected from the critical regions of the performance map. The numerical analysis of the existing compressor is performed at these three points. It is seen that the efficiency error rates between the analysis and the experiment data are %1.6 (OP1), %0.9 (OP2) and %3.1 (OP3). This proves that our CFD model is validated based on the experimental data. The second part of the study is started with an examination of the impeller. Literature studies on increasing the performance of the compressor system are examined in detail. As a result of the literature research, it has been seen that the centrifugal compressor backsweep angle at the outlet of the blade (β2) and total blade number of blades (z) design parameters have significant effects on turbocharger compressor performance. A total of 45 different CFD models are defined for a total of 15 different designs (including the original design) at three different operating points and analyzed on the validated CFD model in order the examine the effect of the blade backsweep angle (β2) at compressor wheel outlet and total blade number combination on performance. For the total number of blades, a total of twelve (six – six (main blades– splitter blades)), a total of fourteen (seven – seven) and a total of sixteen (eight – eight) (original compressor wheel) are examined. In addition, 5 different trailing edge backsweep angles (20°, 22.5°, 25°, 27.5° (original angle of compressor wheel), and 30°) are considered. Within the scope of this thesis, efficiency gains at levels where pressure variation is negligible are taken into account. Efficiency and pressure variations of all designs, including the current impeller design, are evaluated on the same graphs for the same operating points, and the blade backsweep angle is reduced 2.5°, while the total number of blades is reduced from 16 to 14. The results of the analyzes performed with the existing impeller design are compared in terms of compressor outlet pressure and compressor isentropic efficiency. At the first operating point, an increase of 0.78% is achieved in the isentropic efficiency of the compressor when the total outlet pressure variation is 0.58%. In the case where the total outlet pressure change at the second operating point was 0.68% an efficiency increase of 1.98% is achieved. Finally, when the third operating point is examined, a 2.34% improvement in the isentropic efficiency of the compressor is obtained when the total pressure change at the compressor outlet is 0.35%. The greatest efficiency increase is seen in OP2 and the greatest pressure change is observed in OP3.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2021
Keywords: Turbocharger; Centrifugal compressor; Blade backsweep angle; Total number of blades; Performance